Associations between Life's Essential 8 scores and systemic immune-inflammation index among American-adult populations without cardiovascular disease - Huang, Shan-Shan; Yu, Xiao-Shuang; Lin, Tong; Xie, Zhen-Ye; Mao, Hai-Yan; Yang, Zhou-Xin (Frontiers in Medicine, 2025)
BackgroundCardiovascular health (CVH) profoundly impacts human health and quality of life. Increasing evidence suggests a close association between cardiovascular disease (CVD) and systemic immune-inflammatory levels. This study explores the potential correlation between Life's Essential 8 (LE8) scores and the systemic immune-inflammation index (SII), a novel immune-inflammatory index among US adults. This study provides evidence supporting the role of systemic inflammation reduction in promoting CVH.MethodsUtilizing data from the National Health and Nutrition Examination Survey (NHANES) spanning 2007–2018, we investigated information from 21,403 adult participants. Participants were categorized into low CVH (0–49), moderate CVH (50–79), and high CVH (80–100) groups based on LE8 scores. We employed weighted linear regression analysis and subgroup analysis, along with restricted cubic spline curves (RCS) to explore the association between LE8 and SII and the dose-response relationship.ResultA significant negative correlation was found between higher LE8 scores and lower SII levels. Compared to the low CVH group, the β coefficients for SII in the CVH moderate and CVH high groups were −40.02 (95% CI: −58.99 to −21.05, p < 0.001) and −77.62 (95% CI: −102.4 to −52.80, p < 0.001), respectively. Additionally, both LE8 scores and health behaviors scores showed a significant linear negative correlation with SII. There was an inverted “U-shaped” non-linear relationship between health factors scores and SII, and the health factor score was 284.724, with a maximum SII threshold of 518.010 (1,000 cells/μl). The health factor score is positively associated with SII below 518.010 and negatively associated above this threshold. Subgroup analyses showed that the negative association was stable in most subgroups. The negative correlation was insignificant among those aged >65 and Mexican Americans.ConclusionLE8 showed a significant negative correlation with SII. The findings suggest that maintaining higher LE8 scores to some extent promotes CVH and helps alleviate systemic inflammation, potentially benefiting overall health.